Karakteristik Daging dengan Penambahan NaCl pada Berbagai Waktu Aging Post Mortem - Hatta, Wahniyathi; Hermanianto, Joko; Maheswari, Rarah RA (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2006)
It  is  important  to  maintain  meat  characteristics  after  slaughtering  because  its relationship  with  preferences  and  economics  values of  meat  and  meat  product.    Salt addition  is  an  alternative.    The  aim  of  this  research  was  to  observe  influence  of  salt addition  on  meat  characteristics  during  the  first  7  day  of  post  mortem  aging.    Meat sample was divided into three groups of salt added treatments : 1) without salt addition, 2) salt added at one  day prior to aging, and 3) salt added every day along aging period.  The results showed that salt added at the zero day was to increase pH, solubility of salt-soluble  protein,  and  water  holding  capasity  (WHC)  to  a higher  level  compared  to  the other two treatments.  Although salt  addition may increased the meat characteristics, decreasing these characteristics could not be avoided when the meat stored for 7 day post mortem aging.